Fear and the making of foreign policy : Europe and beyond - Taras, Ray, 1946- (Edinburgh University Press, 2015)
This is a book about conflicts and fears: how domestic reasons are drawing countries in Europe into international events. There has been much research into why the U.S. and U.K. militaries intervened in Iraq, Afghanistan, and other conflict zones. But what explains France's newfound international activism, which is taking its military to Libya, Mali and deeper into Africa? Why has Poland become deeply engaged in Ukraine's politics? Why is Sweden, which has not fought a war since 1814, concerned with the fierce internal wars in Iraq and Syria? Can these actions be explained as countries simply protecting their national interests, or could domestic xenophobia also be playing a part? In Fear and the Making of Foreign Policy, Raymond Taras explains the causal mechanisms propelling these three EU states to become engaged in outside conflicts and tells the story of when and why xenophobia at home is converted into xenophobia abroad. Key Features. Chapter-length case studies of France, Poland and Sweden, with counterpoints from the USA, China, Iran and Turkey, investigate the role that human phobias play in international politics Examines states in Europe and beyond that have been marked by contrasting historical pathways, and whose policy responses to 'strangers' at home and to 'friends' or 'foes' abroad are dramatically dissimilar Addresses the phenomena of social fears, moral panic and declinism of the West through the prism of xenophobic attitudes and their often underestimated consequences
Keywords: European Union countries -- Foreign relations.; Xenophobia -- Europe.; Pays de l'Union européenne -- Relations extérieures.; Xénophobie -- Europe.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; POLITICAL SCIENCE -- Comparative Politics.; Diplomatic relations; Xenophobia; Europe; European Union countries; Electronic book.